Divinity and state - Womersley, David (Oxford : Oxford University Press, 2010)
This text explores how the Reformation's transformation of religious belief into a political statement and the saturation of the national past with religious implications (created by the political developments of the 1530s) was reflected in 16th-century English historiography and historical drama.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Religion and drama -- History -- 16th century; Reformation -- England; Church and state -- England -- History -- 16th century; Great Britain -- History -- Tudors, 1485-1603 -- Historiography; Religion in literature -- History -- 16th century; Church and state in literature -- History -- 16th century